Early class III protraction facemask treatment reduces the need for orthognathic surgery: a multi-centre, two-arm parallel randomized, controlled trial. (2nd July 2016) - Mandall, Nicky; Cousley, Richard; DiBiase, Andrew; Dyer, Fiona; Littlewood, Simon; Mattick, Rye; Nute, Spencer J.; Doherty, Barbara; Stivaros, Nadia; McDowall, Ross; Shargill, Inderjit; Worthington, Helen V.
Abstract : Objective : To evaluate whether patients who had received early class III protraction facemask treatment were less likely to need orthognathic surgery compared with untreated controls. This paper is a 6-year follow-up of a previous clinical trial.Design : Multi-centre 2-arm parallel randomized controlled trial.Setting : Eight United Kingdom hospital orthodontic departments.Participants : Seventy three 7- to 9–year-old children.Method : Patients were randomly allocated, stratified for gender, into an early class III protraction facemask group (PFG) ( n = 35) and a control/no treatment group (CG) ( n = 38). The primary outcome, need for orthognathic surgery was assessed by panel consensus. Secondary outcomes were changed in skeletal pattern, overjet, Peer Assessment Rating (PAR), self-esteem and the oral aesthetic impact of malocclusion. The data were compared between baseline (DC1) and 6-year follow-up (DC4). A per-protocol analysis was carried out with n = 32 in the CG and n = 33 in the PFG.Results : Thirty six percent of the PFG needed orthognathic surgery, compared with 66% of the CG ( P = 0.027). The odds of needing surgery was 3.5 times more likely when protraction facemask treatment was not used (odds ratio = 3.34 95% CI 1.21–9.24). The PFG exhibited a clockwise rotation and the CG an anti-clockwise rotation in the maxilla (regression coefficient 8.24 (SE 0.75); 95% CI 6.73–9.75; P < 0.001) and the mandible (regression coefficient 6.72 (SE 0.73); 95% CI 5.27–8.18; P < 0.001). Sixty eight per cent of the PFG maintained a positive overjet at 6-year follow-up. There were no statistically significant differences between the PFG and CG for skeletal/occlusal improvement, self-esteem or oral aesthetic impact.Conclusions : Early class III protraction facemask treatment reduces the need for orthognathic surgery. However, this effect cannot be explained by the maintenance of skeletal cephalometric change.